2019
DOI: 10.1111/apa.14796
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure in children with severe pneumonia and hypoxaemia in Papua New Guinea: an evaluation of implementation

Abstract: Aim To prospectively evaluate the use of bubble continuous positive airway pressure (CPAP) in children with very severe pneumonia and other acute lower respiratory infections, during its trial introduction in a low resource hospital in Papua New Guinea. Methods Prospective observational study of children treated with CPAP who had severe pneumonia and severe respiratory distress with hypoxaemia (SpO2 <90%). CPAP was driven by oxygen concentrators in which the fraction of inspired oxygen could be adjusted, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 21 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…A total of 2174 studies were screened and 20 met criteria for inclusion (Figure 1). These included five randomized control trials (RCTs) [9][10][11][12][13] , one cluster RCT 14 , one non-randomized comparative study 15 , eleven observational studies [16][17][18][19][20][21][22][23][24][25][26] (prospective and retrospective observational studies and case series) and two case reports 27,28 (Table 2). A majority of the studies evaluated the use of NIV in the form of bubble CPAP (bCPAP) or conventional nasal CPAP (nCPAP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2174 studies were screened and 20 met criteria for inclusion (Figure 1). These included five randomized control trials (RCTs) [9][10][11][12][13] , one cluster RCT 14 , one non-randomized comparative study 15 , eleven observational studies [16][17][18][19][20][21][22][23][24][25][26] (prospective and retrospective observational studies and case series) and two case reports 27,28 (Table 2). A majority of the studies evaluated the use of NIV in the form of bubble CPAP (bCPAP) or conventional nasal CPAP (nCPAP).…”
Section: Resultsmentioning
confidence: 99%
“…Four of these studies, all of which took place at tertiary hospitals, reported mortality rates >30%. 18, [24][25][26] Mortality was the primary endpoint for five prospective observational studies and was 2% 16 , 10% 17 , 29% 23 , 33% 24 , and 47%. 26 Multiple comorbidities likely play a detrimental role in outcomes, as evidenced by the study with the highest mortality rate (47%), which showed much lower mortality rates among lower risk patients (18% rate in HIV-uninfected and only single organ failure).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe such formal curricula need to be complemented by an accessible library of methods and interventions illustrated by implementation examples from LRS. 5 31 34 One critical task though is to empower national leaders, possibly through their national professional organisations, so they can offer the coaching, mentorship and support to local leaders that is needed. Where necessary, this may be facilitated by international collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…This requires making sure key clinical tasks, such as monitoring, are carried out regularly and reliably. 5 To achieve this however, it may be necessary to strengthen the underlying system by, for instance, clarifying policies and team responsibilities. In addition to this, placing restrictions on when CPAP can be used makes care safer for the whole population of newborns in the unit.…”
Section: Introductionmentioning
confidence: 99%